MENGHUBUNGKAN INOVASI DAN MASYARAKAT: PENGEMBANGAN E-MARKETPLACE PKM UNIVERSITAS TERBUKA - Prakoso, Teguh; Nursantoso, Teguh; Permanasari, Devi; Rovandi, Harris; Mustari, Mustari; Heriani, Heriani; Lase, Sepandil Laras (Jurnal Abdimas Bina Bangsa, 2025)
Community Service (PkM) is one of the pillars in the tridharma of higher education which aims to provide a real impact on society. This study develops an e-marketplace application "Gallery PkM Universitas Terbuka" as a solution to improve the marketing of products resulting from community service. The method used is Rapid Application Development (RAD), which allows rapid application development with repeated iterations. The results of the study show that this application makes it easy for students, lecturers, and the community to access and market products. The trial of Universitas Terbuka students showed a satisfaction level of 73.14%, which is included in the "Good" category. However, there are several aspects that need to be improved, such as improving image editing features, optimizing product displays, and developing payment options. With this application, it is hoped that the marketing of PkM products can be more optimal, expanding reach, and increasing the economic independence of the community.